Curative Management of Malignant Left-Sided Colorectal Obstruction - Wen-Shen Lee; Joseph C. Kong; Peter Carne; Stephen Bell; Satish K. Warrier (World Journal of Colorectal Surgery)
Left-sided malignant colonic obstruction remains a challenging surgical problem despite recent advances. We aim to provide a concise overview of the relevant surgical options for this condition in the curative setting. A literature search of MedLine, PubMed, and Embase was performed to elucidate the latest evidence in the management of malignant left-sided colorectal obstruction, focusing on the risks and benefits of each approach and the appropriate patient selection. Primary resection and anastomosis are the intervention of choice for low-risk patients in the curative setting. Delayed resection with a bridge to surgery should be considered in unwell patients requiring medical optimization. While stenting has gained popularity, the risk of stent perforation carries a poor prognosis and must be carefully considered. Hartmann's procedure should be considered in high-risk elderly patients. Subtotal colectomy is preferred over segmental colectomy when there is extensive proximal colon damage but results in more frequent bowel actions postoperatively.